2017
DOI: 10.1097/prs.0000000000003325
|View full text |Cite
|
Sign up to set email alerts
|

A Formidable Foe Is Sabotaging Your Results: What You Should Know about Biofilms and Wound Healing

Abstract: Learning Objectives After reading this article, the participant should be able to: 1. Describe biofilm pathogenesis as it relates to problem wounds, 2. Understand the pre-clinical and clinical evidence implicating biofilm in problem wounds, 3. Explain the diagnostic and treatment challenges that biofilms create for problem wounds, 4. Demonstrate a basic understanding of emerging strategies aimed at counteracting these processes. Summary Biofilm represents a protected mode of growth for bacteria, allowing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 81 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…This suggests that, in this rodent model, the ongoing P . aeruginosa infection associated with the foreign body led to continuous breakdown of the overlying integument 72 . This had already been amply observed in clinical practice 72,78 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that, in this rodent model, the ongoing P . aeruginosa infection associated with the foreign body led to continuous breakdown of the overlying integument 72 . This had already been amply observed in clinical practice 72,78 .…”
Section: Discussionmentioning
confidence: 99%
“…This lends support to the notion that in bacteria capable of producing biofilms, such as P . aeruginosa , the protracted release of bacterial cells from the biofilm medium is one of the main determinants of continuous tissue damage to the overlying tissues 45,60,7274 . In fact, a recent meta-analysis demonstrated that biofilms are present in more than three quarters of chronic wounds, increasing their extension or preventing their closure 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Infection with biofilm is not necessarily accompanied by the cardinal signs of inflammation such as pain, redness, heat, and swelling, and many studies have tried to identify specific clinical signs related to biofilm-infected chronic wounds. However, signs vary, and no specific clinical signs have been found to correlate with biofilm infection [10,18,26,[91][92][93], which makes it extremely difficult for clinicians to evaluate whether wounds are infected with biofilm.…”
Section: Detection Of Biofilm In Woundsmentioning
confidence: 99%
“…The prevalence of biofilms in chronic wounds according to recent meta-analysis has been reported to be 78.2%, with some cases recording a higher rate of infection [ 15 , 16 ]. Bacterial infection triggers inflammation at the injury site following the recognition of bacterial antigen or secreted products, such as proteolytic enzymes [ 17 , 18 ]. The abnormal level of infection rate contributes to the delay in wound healing by prolonging the inflammatory phase as the immune cells attempt to clear the infection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%